Location as a Competitive Advantage to Attract Students: An Empirical Study from a Turkish Foundation University - Aydın, Oya Tamtekin (International Review of Management and Marketing, 2013)
The purpose of this study is to reveal whether the location is a sustainable competitive advantage to attract the students or not. This study consists of a literature review about location in higher education area, research about a sample Turkish foundation university enrollment records and a survey on students attending a sample foundation university in Istanbul. The questionnaire method has been chosen in order to show the importance of location for a university. The students had been admitted to a foundation university in the 2013-2014 period when within the same universities various departments almost the same score in exam were included in the study. The results of study indicate the location affects the students’ university choice decision and so it is a kind of sustainable competitive advantage for this sample university. This paper proposes the location has an important effect to attract the students to universities. This will help the university manager’s decision-making on the strategic planning. This study has revealed one important competitive advantage criteria for foundation universities. Keywords: Sustainable competitive advantage; location; universities; Turkey JEL Classifications: I23; M1; R3